Maintain the schooling of school refusers: conceptualization of a school reception protocol using digital technology. - Angélique Ferrandon-Vépierre; Inès Di Loreto; Yann Verchier (Interaction Design and Architecture(s))
School Refusal (SR) can affect one pupil per class and last for several months or years. These pupils, who are more or less absent from school, represent a major challenge for schoolteachers, who find it difficult to understand these disorders and put in place solutions to keep them in school. For their part, SR pupils talk about the need to be able to build a future for themselves at school. An in-school reception protocol with face-to-face and distance learning sessions is drawn up on the basis of the needs of the pupils and the difficulties of dealing with them in the school environment. A contact person ensures good communication between all those involved. Digital technology is proposed as a mediator between the teachers, who send the educational content provided in class, and the anxious pupils who refuse to attend school. In this way, a new ecological intervention and monitoring system based on a program of actions has been devised to meet the needs of SR pupils.